What effect does public and private capital have on income inequality? The case of the Latin America and Caribbean region - Renato Santiago; José Alberto Fuinhas; António Cardoso Marques; Matheus Koengkan (Latin American Economic Review, 2022)
The effects that the Latin America and Caribbean capital stock (public and private) had on the income inequality levels of 18 countries from this region were analyzed, over a period ranging from 1995 to 2017, recurring to an autoregressive distributed lag model in the form of an unrestricted error correction model. The results from the three models that were estimated (with the total capital stock, the public capital stock, and the private capital stock) pointed for the existence of an enhancing effect from the capital stock (public and private) on the income inequality of these countries in the short-run, suggesting that the investments were made in the already richer/wealthiest areas. In the long-run, the effects of capital stock on income inequality seem to vanish, probably due to the efforts to correct the previous detrimental effect. However, the lack of a statistically significant impact shows that, although the efforts, capital stock (public and private) still does not contribute to the income inequality reduction, meaning that these countries should improve/change the management and the selection criteria of their physical capital investments to be able to reduce their income gap.
Keywords: 330; income inequality; public capital stock; private capital stock; Latin American and the Caribbean countries